Perdedaan Terapi Massage dan Terapi Relaksasi dalam Mengurangi Nyeri Persalinan di Bidan Praktik Swasta (BPS) Ernawati Kecamatan Banyumas - Sunarsih Sunarsih; Ernawati Ernawati (Jurnal Kesehatan, 2017)
Labor Pain can cause uncoordination of uterus activity, it led long labor and finally threaten fetus’ and mother’s life.Various efforts were done to relieve the pain at labor, such as massage therapy and relaxed technique. The survey result at Ernawati’s Health Centertoward, there were five labor’s women, 80% of them said that they felt pain which could not be endurable at the time of labor process, but it relieved after done massage and relaxation. This research was to known difference of massage and relaxed therapy in relieving labor pain at Ernawati’s Health Center, BanyumasSubdistrict, in 2016. it was quantitative research by quasi-experimental design, held on 12th March  to 25th July 2016. Population were all mothers who would give a birth, about 31 women, total sample were 40 women. Sampling technique was systematic sampling technique. The variables in this study were massage therapy, relaxed techniques and labor pain. Data analized by using T-test. The result showed that the average of labor pain before and after given massage were 6,90 and 4,90, respectively. Mean differences was 2,0. Then, the average of labor pain before and after given relaxed technique were 6,90 and 5,25, respectively. Mean differences was 1,65. The result of statistic test, p-value=0,000. It means that there were difference between massage and relaxed therapy in relieving labor pain at Ernawati’s Health Center, BanyumasSubdistrict in 2016.